A biocultural approach to literary theory and interpretation - Easterlin, Nancy (Johns Hopkins University Press, 2012)
Combining cognitive and evolutionary research with traditional humanist methods, Nancy Easterlin demonstrates how a biocultural perspective in theory and criticism opens up new possibilities for literary interpretation.